Islam and Minorities: Managing Identity in Malaysia - Ahmad Suaedy (Al-Jami'ah Research Centre, 2010)
The Malaysian general election in March 2008 raised an interesting and new phenomenon. For the first time since independence in 1957, the ruling alliance known as the National Front (Barisan Nasional, BN) failed to secure two thirds of seats in parliament and lost control of five of Malaysia’s 13 states. This was due to the challenge presented by the new opposition alliance known as the Alternative Front (Barisan Alternatif, BA) or the People’s Alliance (Pakatan Rakyat, PK) which won more than 36% of seats in parliament and gained control of the five states. In the 2004 election, BN secured the largest ever percentage of seats in parliament with 91%. What is interesting is that it seems that this significant increase in support for the opposition is due to their offer to change the way minorities and ethnicity is managed. They propose a move from “Bumiputera Supremacy”, or affirmative action for the approximately 65% of “Bumiputera” Malaysians (the rest being largely of Chinese or Indian ethnicity), to “The People’s Supremacy”, which involves eradicating affirmative action based on ethnicity, basing it instead on need, for instance need due to poverty. This would potentially increase the likelihood of justice and equality for all ethnic or racial groups. This paper connects the phenomenon of change, as seen in the about turn in the results between the 2004 and 2008 elections, to the more global trend in which minorities are standing up to demand their rights in this era of globalization, and to the challenge multiculturalism presents to parts of the Muslim world such as Malaysia. Malaysia, a Muslim majority nation that has formally declared Islam the official state religion with Yang di-Pertuan Agong (the King) as Head of the State and symbol of Islam, is one example, though not necessarily representative, of how Islam and Muslims manage minorities and identity or multiculturalism within the process of globalization.